Discussion of Square Wave Control Technology for Permanent Magnet Synchronous Motor - WEN Yuliang; ZHENG Hanfeng; HUANG Jiade; HE Yaping; FENG Jianghua (机车电传动)
Permanent magnet synchronous motor (PMSM) has the outstanding advantage of full voltage output in square wave mode, which can greatly improve the output power of the system, especially for high speed and high power applications. However, the common square wave control has some shortcomings such as mode switching and poor dynamic performance. By using modulation linearization, adding fundamental current observer and dynamic flux weakening technology, the vector control method of full speed permanent magnet synchronous motor was unified. Simulation results showed that the proposed method has high performance torque response capability under square wave conditions.